THE CHARACTERISTICS OF THE RELATION BETWEEN THE PORT ACTIVITIES AND URBAN CONFLICTS IN THE MUNICIPALITY OF SÃO SEBASTIÃO / SP - Rodrigues, Edson Wagner; Santos, Moacir José dos (RBGDR, 2019)
Port activities have the potential to define the conditions of development of the locations and regions where they are installed. This premise shaped the research presented in this article. The objective corresponds to the characterization of the relation between port activities and urban conflicts in the municipality of São Sebastião / SP. The method used was the case study with an analysis of the secondary data and public documents pertinent to the port activities carried out in the municipality. As a result, it was demonstrated that São Sebastião port is a local vector for economic growth and urban expansion. The history of anthropic actions established a policy of intervention in the space through landfills (increased marina), promoting a disorderly occupation in the surroundings of the port with dwellings characterized by precariousness and insalubrity due to the absence of public policies dedicated to the adequate absorption of the population growth. It is concluded that the articulation of productive port activities in the city established a process of imbalance in the economic and social relationships underlying the urban conflicts in the municipality.